Degradasi Zat Warna Methylene Blue Dengan Metode Fotofenton Menggunakan Katalis nano-Fe0@CS - Rahman Fikri; Panca Setia Utama; Edy Saputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
In this study, nano-Fe0@CS were synthesized by hydrothermal method. Studied Methylene Blue (MB) degradation process and find the best composition of the degradation process. Catalytic performance of nano-Fe0@CS was tested in Phenton process for MB degradation in aqueous solution with H2O2 3%, and MB concentration variant. The best process conditions was observed by 99.99% removal of 30 ppm MB within 90 min with added 0.3 g/l nano-Fe0@CS and 2 ml H2O2 3% in 250 ml solution.Keywords: Degradation, Methylene Blue, nano-Fe0@CS, Phenton Process